Manufacturing in Sindh: Growth and Spatial Distribution - Muhammad Jawed Iqbal; Syed Shahid Ali (Journal of Basic & Applied Sciences, 2015)
Manufacturing is significantly important in Sindh. It is a major contributor of the GDP along with the agriculture sector. Industrial development of Sindh occurred after the emergence of Pakistan and manufacturing gained considerable size in the recent years as a major economic activity in the province. The paper focuses on chief aspects i.e. growth and concentration pattern. The trends and rate of growth have been analyzed over a period of thirty years beginning 1975-76. The spatial pattern is shown by the technique of location quotient which measures the extent of concentration of manufacturing in the districts of Sindh. Three districts i.e. Karachi, Dadu and Hyderabad emerge as major industrial concentrations.